2016
DOI: 10.1177/1359105315600236
|View full text |Cite
|
Sign up to set email alerts
|

The importance of health(ism): A focus group study of lesbian, gay, bisexual, pansexual, queer and transgender individuals’ understandings of health

Abstract: This study investigated understandings of health among lesbian, gay, bisexual, pansexual, queer and/or transgender people, who are under-represented in research. The study involved 12 focus groups in Aotearoa/New Zealand with 47 participants who identified as lesbian, gay, bisexual, pansexual, queer and/or transgender and responded to an advert inviting participants without chronic illnesses. Three themes were inductively formulated: health is important because education and protection efforts are seen as requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
(65 reference statements)
0
6
0
1
Order By: Relevance
“…Alongside these social shifts, researchers have underscored the importance of identifying and recognizing the health disparities experienced by sexual and gender minorities (Institute of Medicine [IOM], 2011;Meyer, 2003). Compared to the health disparities literature focused on gay, bisexual and other men who have sex with men, there has been limited research attending to the psychosocial needs of other sexual and gender minority subgroups (Graham, Treharne, Ruzibiza, & Nicolson, 2017), including sexual minority women (SMW; i.e., women with same-sex attractions and/or who identify as nonheterosexual). Sexual minority women are less likely to have insurance and report lower rates of overall good health (U.S. Department of Health and Human Services, 2011), annual physical exams (Blosnich, Farmer, Lee, Silenzio, & Bowen, 2014), and cervical cancer screenings (IOM, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside these social shifts, researchers have underscored the importance of identifying and recognizing the health disparities experienced by sexual and gender minorities (Institute of Medicine [IOM], 2011;Meyer, 2003). Compared to the health disparities literature focused on gay, bisexual and other men who have sex with men, there has been limited research attending to the psychosocial needs of other sexual and gender minority subgroups (Graham, Treharne, Ruzibiza, & Nicolson, 2017), including sexual minority women (SMW; i.e., women with same-sex attractions and/or who identify as nonheterosexual). Sexual minority women are less likely to have insurance and report lower rates of overall good health (U.S. Department of Health and Human Services, 2011), annual physical exams (Blosnich, Farmer, Lee, Silenzio, & Bowen, 2014), and cervical cancer screenings (IOM, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…O reconhecimento e a proteção dos direitos humanos são os pilares de sustentação de uma democracia 8 . Nas publicações revisadas, discutiu-se a importância dos ativismos LGBTT nas lutas pelos direitos humanos no campo da saúde e, por conseguinte, nas lutas por transformar, em um sentido positivo, as próprias condições contextuais e intrínsecas aos serviços e às práticas profissionais que influenciam o acesso e a qualidade da assistência à saúde LGBTT 45,46,51 .…”
Section: A Dimensão Contextualunclassified
“…Internationally, the mental health needs of the lesbian, gay, bisexual and transgender (LGBT) communities have been largely overlooked. Much of the health focus for these communities have been on sexual health issues, primarily human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) (Cicero et al., 2020; Graham et al., 2017; Neville & Henrickson, 2006). It has been suggested that this limited focus is a consequence of heterosexualism and homophobic bias, resulting in a lack of research around the specific health needs of the LGBT communities (Treharne & Adams, 2017).…”
Section: Introductionmentioning
confidence: 99%